2018
DOI: 10.1111/bpa.12613
|View full text |Cite
|
Sign up to set email alerts
|

Grading of meningeal solitary fibrous tumors/hemangiopericytomas: analysis of the prognostic value of the Marseille Grading System in a cohort of 132 patients

Abstract: The finding that meningeal solitary fibrous tumors (SFTs) and meningeal hemangiopericytomas (HPCs) are both characterized by NAB2-STAT6 gene fusion has pushed their inclusion in the WHO 2016 Classification of tumors of the central nervous system (CNS) as different manifestations of the same entity. Given that the clinical behavior of the CNS SFT/HPC spectrum ranges from benign to malignant, it is presently unclear whether the grading criteria are still adequate. Here, we present the results of a study that ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 51 publications
2
27
0
7
Order By: Relevance
“…Furthermore, incorporating necrosis into ST-G, i.e., classifying tumors based on mitotic rate and necrosis, seems to improve the outcome models when compared to mitotic rate alone. In their recent work from 2018, Macagno et al sought to validate an updated version of the Marseille Grading Scheme which segregated 132 tumors into three groups based on mitotic activity (≥ 5 mitotic figures/10 HPF) and necrosis [4, 15]. On univariate analysis, they found that extent of surgery, radiotherapy/chemotherapy, and mitotic rate were significant in predicting RFS, while radiation, mitotic rate, and necrosis were significant for disease-specific survival [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, incorporating necrosis into ST-G, i.e., classifying tumors based on mitotic rate and necrosis, seems to improve the outcome models when compared to mitotic rate alone. In their recent work from 2018, Macagno et al sought to validate an updated version of the Marseille Grading Scheme which segregated 132 tumors into three groups based on mitotic activity (≥ 5 mitotic figures/10 HPF) and necrosis [4, 15]. On univariate analysis, they found that extent of surgery, radiotherapy/chemotherapy, and mitotic rate were significant in predicting RFS, while radiation, mitotic rate, and necrosis were significant for disease-specific survival [15].…”
Section: Discussionmentioning
confidence: 99%
“…In their recent work from 2018, Macagno et al sought to validate an updated version of the Marseille Grading Scheme which segregated 132 tumors into three groups based on mitotic activity (≥ 5 mitotic figures/10 HPF) and necrosis [4, 15]. On univariate analysis, they found that extent of surgery, radiotherapy/chemotherapy, and mitotic rate were significant in predicting RFS, while radiation, mitotic rate, and necrosis were significant for disease-specific survival [15]. Extent of surgery and mitotic rate remained significant prognostic factors for RFS with multivariate analysis, while necrosis and radiotherapy were significant for disease-specific survival [15].…”
Section: Discussionmentioning
confidence: 99%
“…Michele et al advocated inclusion of high Ki-67 (i.e. > 5%) as an adverse prognostic parameter in assessing the prognosis of SFT of the CNS [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Grading of meningeal solitary fibrous tumors/hemangiopericytomas (SFTs/HPCs) of the central nervous system (CNS) is nowadays based on histologic criteria as described in the revised fourth edition of the WHO Classification of CNS tumors [10] or the more recently published, updated version of the Marseille Grading System (MGS) [11]. Histology based grading of CNS SFTs/HPCs allows for discriminating subgroups with significant differences in prognosis.…”
mentioning
confidence: 99%
“…To evaluate the prognostic value of NAB2-STAT6 fusion variants and TERT promoter mutations for CNS SFTs/HPCs, we retrospectively analyzed these markers in a cohort of136 patients with STAT6 nucleopositive CNS tumors. All tumors were graded according to the most recent WHO classification [10] and the updated MGS [11] and were analyzed for type of NAB2-STAT6 fusion and the presence of TERT promoter mutation. For NAB2-STAT6 fusion analysis, we performed reverse transcriptase polymerase chain reaction (RT-PCR) after RNA extraction and cDNA synthesis using multiple primer sets finding the most common fusion variants which were subsequently grouped based on their hypothesized functional effects [3,15].…”
mentioning
confidence: 99%